Management of Woman with Placenta Accreta - Ranabhat, Radha (Journal of Nursing Education of Nepal, 2011)
A placenta accreta is an abnormally invasive implantation of the placenta into the uterine wall. It occurs when the chorionic villi invade the myometrium. This condition affects 1 in 2500 pregnancies (ACOG, 2002). Its risk factors include advanced maternal age and a history of previous cesarean deliveries. (De, LM. 2004) There has been an increase in the incidence of placenta accrete in recent years most likely due to recent increases in cesarean deliveries. The deep adherence of the placenta makes it difficult to detach, which puts the mother at high risk for hemorrhage during delivery. For this reason, placenta accreta may require a hysterectomy. Sonography is used as a screening image the fetus and placenta; however, magnetic resonance imaging (MRI) is often used when placenta accreta is suspected because it can help differentiate the specific type of invasive placental implantation. Prenatal diagnosis can help healthcare professionals prepare for the expected complications during delivery, thereby reducing morbidity and mortality of the mother.
Keywords: NA